The Man Utd Miscellany - Mitten, Andy (London Vision Sports Publishing, 2008)
Which United legend got fined for cycling with no lights? What happened when aliens invaded Old Trafford? This book contains stats, lists, quotes, anecdotes and tables from the rich history of Manchester United. It includes a color kits section, and a complete history of the club's home and away kits.
Include Sketches.
English Fiction.
Keywords: Manchester United (Soccer team) -- Soccer teams -- England--Manchester